PENGARUH MODAL SOSIAL TERHADAP KINERJA KELOMPOK TANI DALAM PENERAPAN PTT PADI SAWAH (Oryza sativa L) DI DESA KOKOSAN KECAMATAN PRAMBANAN KABUPATEN KLATEN - Dewi Fortuna, Puri Eka (Jurnal Ilmu-Ilmu Pertanian, 2019)
This study aims to determine the social capital that exists in farmer groups and analyse the effect of social capital on the performance of farmer groups in the implementation of Integrated Plants Management of Rice Paddy in Kokosan Village, Prambanan District, Klaten Regency. The method used in this research is survey. Determination of village location was done purposively, namely villages that had carried out activities related to Integrated Plants Management of Rice Paddy. The sampling technique was carried out by proportional random sampling totalling 34 respondents. Data were analysed descriptively and multiple linear regression. The results of the study show that social capital consisting of participation, trust, and cooperation significantly influences the performance of farmer groups in the application of rice paddy integrated plants management in Kokosan Village, Prambanan District, Klaten Regency with a total influence of 68.1%. Partially variable of participation directly affects a significant result of 0,020 and the descriptive study results of 78,92% with always category. Trust doesnt directly affect the substantial result of 0,129 and the descriptive study results of 79,12% with always category. Cooperation directly affects a significant result of 0,017 and the descriptive study results of 78,73% with always category. The variables that make the greatest contribution are trust on the performance of farmer groups in the implementation of Integrated Plants Management of Rice Paddy. The results of the largest coefficients are ranking in cooperation, trust and participation.